[Labor Management Committee's monthly checks] - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Memorandum from William Adams to Susan Stuntz on January 18,1989, regarding the Labor Management Committee's checks. Identifies several amounts to be made out to different organizations on the first of every month.